The main objective of this study is to analyze the structural change pattern and source of growth in the West Java economy 1993-2003 period. The analysis was using econometric, IO (input-ouput) and SAM (social accounting matrix) approach. The results of this study are: (1) economic structural transformation are drawn by declining of agriculture share both in output and employment, and household income distribution in this province are not equal, and (2) source of output growth are dominated by - Eko Wahyu Nugrahadi; Mangara Tambunan; Hermanto Siregar; Arief Darjanto (Forum Pasca Sarjana, 2010)
The main objective of this study is to analyze the structural change pattern and source of growth in the West Java economy 1993-2003 period.  The analysis was using econometric, IO (input-ouput) and SAM (social accounting matrix) approach.  The results of this study are: (1) economic structural transformation are drawn by declining of agriculture share both in output and employment, and household income distribution in this province are not equal, and (2) source of output growth are dominated by domestic final demand and export, while employment growth are dominated by labour intensity and technical coefficient.  The implication of this study is maintain industrialization policy through ADLI and export promotion industry strategy.   Key words: structural change pattern and source of growth